Indicators of inequality and poverty - S. Subramanian (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This essay aims at a broad, main-stream account of the literature on inequality and poverty measurement in the space of income and, additionally, deals with measures of disparity and deprivation in the more expanded domain of capabilities and functionings. In addition to an introductory and a concluding part, the paper has four sections. The first of these, on measurement of income inequality, deals with preliminary concepts and definitions; a visual representation of inequality (the Lorenz curve); real-valued indices of inequality; properties of inequality indices; some specific inequality measures; and the relationship between Lorenz, welfare, and inequality orderings. The second section, on poverty, deals with the identification and aggregation exercises; properties of poverty indices; some specific poverty measures; the problem of plurality and unambiguous rankings; poverty measures and anti-poverty policy; and other issues in the measurement of poverty. The third section considers aspects of both congruence and conflict in the relationship amongst poverty, inequality, and welfare. The final substantive section advances the rationale for a more comprehensive assessment of human wellbeing than is afforded by the income perspective, it briefly reviews measurement concerns relating to generalized indices of deprivation and disparity, and it discusses the data and policy implications of the more expansive view of well-being adopted in the section.
Keywords: D63; I31; I32; 330; inequality; disparity; poverty; deprivation; measurement; income; capability; functioning; well-being; Einkommensverteilung; Armut; Sozialer Indikator